2014
DOI: 10.1016/j.nrl.2013.07.007
|View full text |Cite
|
Sign up to set email alerts
|

Cefaleas en la persona mayor: características de una serie de 262 pacientes

Abstract: Elderly patients were frequently treated in our outpatient headache unit. Tension-type headache was the most common diagnosis in this population. Geriatric headache syndromes such as hypnic headache or occipital neuralgia were also represented in our series.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
14
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 34 publications
1
14
0
2
Order By: Relevance
“…The importance of migraine with aura in geriatric patients is still a topic of debate (16). Migraine is closely related to ischemic and hemorrhagic stroke risk, hearth diseases, retinal vasculopathies, and high mortality (17).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The importance of migraine with aura in geriatric patients is still a topic of debate (16). Migraine is closely related to ischemic and hemorrhagic stroke risk, hearth diseases, retinal vasculopathies, and high mortality (17).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, chronic use and over use of analgesics including NSAIDs can trigger headaches (17). The prevalence in geriatric population is between 1%-1.7% (6).…”
Section: Discussionmentioning
confidence: 99%
“…Another study estimates the prevalence of TTH in developed countries to be 66.7 % in males and over 80 % in females [ 17 ]. While Zhao et al report that the peak incidence of TTH occurs between the ages of 30 and 39 in men and women in China [ 18 ], this form of primary headache is still the most common type among the elderly [ 19 , 20 ]. Additional research regarding TTH among the elderly supports this wide variability in prevalence, as studies have found 1-year prevalence rates among individuals older than 50 years of age to be between 16 and 44 % [ 8 , 21 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…We also investigated the prevalence of headaches that could not be classified based on the study participants’ responses. According to previously available data, the prevalence of UNC in older individuals is higher than rates for TTH and MIG [ 20 ]. In our research, 3.63 % of participants reported symptoms of UNC.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore the data presented deserve to be confirmed on data from multicenter cohorts. Nevertheless, in consideration of the close relationship between GCA and PMR, WH of recent onset – even if not associated with raised inflammatory markers in PMR patient – should be considered as a possible manifestation of overlapping GCA and specific diagnostic investigations implemented [17, 18]. …”
Section: Discussionmentioning
confidence: 99%